Rare Case Report: Chondrosarcoma Arising from Osteochondroma in MHE patient. - Simanjuntak, Charles A; Hartanta, Sutiansi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2015)
This is a unique case of chondrosarcoma. From this case, we learn that, Multiple Hereditary Exostoses have strong connection with familial bond. This disease has male predominance, but in this case, the family don’t have any son, and the father are healthy without any sign and symptoms of lumps. As a physicians, it is important to take careful examinations if a patient complain of any bony lump, then it is necessary to take careful and thorough examination of the patient’s body, to know if there are other lumps in the patient’s body, because the chances of getting malignant transformations are bigger in patients who have multiple exostoses, than from patient with single exostose.